Transformasi Media Lensatara: Google Lens dalam Pembelajaran Bagi Mahasiswa - Rachmayanti, Irma; Arifin Alatas, Mochamad (IAIN Madura, 2025)
This research aims to describe the use of Google Lens in translating Arabic for students of the Foreign Language Development Program (FLDP) at IAIN Madura. This study focuses on three main aspects: effectiveness, efficiency, and translation accuracy using Google Lens. The research uses a descriptive approach, with data collected through questionnaires given to students and direct observation of the use of the application. The results indicate that the use of Google Lens is effective in helping students understand Arabic and efficient in terms of time and resources used. Although the translation accuracy does not reach 100%, students are still able to comprehend the meaning of the translated text. Therefore, Google Lens can be a useful tool in supporting Arabic language learning at IAIN Madura, although there is still room for improvement in terms of translation accuracy. This study contributes to the development of technology in foreign language education, particularly in the context of Arabic language teaching at higher education institutions.